7 Units.
8(1)+9= 17
8(2)+9=25
8(3)+9=33
33-25=7. 25-17=7
Answer:-25c+15b+5 ..add it up then boom you'll get your answer
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
I GOT THE POWER OF GOD AND ANIME ON MY SIDE
I assume there are some plus signs that aren't rendering for some reason, so that the plane should be
![x+y+z=1](https://tex.z-dn.net/?f=x%2By%2Bz%3D1)
.
You're minimizing
![d(x,y,z)=\sqrt{(x-4)^2+y^2+(z+5)^2}](https://tex.z-dn.net/?f=d%28x%2Cy%2Cz%29%3D%5Csqrt%7B%28x-4%29%5E2%2By%5E2%2B%28z%2B5%29%5E2%7D)
subject to the constraint
![f(x,y,z)=x+y+z=1](https://tex.z-dn.net/?f=f%28x%2Cy%2Cz%29%3Dx%2By%2Bz%3D1)
. Note that
![d(x,y,z)](https://tex.z-dn.net/?f=d%28x%2Cy%2Cz%29)
and
![d(x,y,z)^2](https://tex.z-dn.net/?f=d%28x%2Cy%2Cz%29%5E2)
attain their extrema at the same values of
![x,y,z](https://tex.z-dn.net/?f=x%2Cy%2Cz)
, so we'll be working with the squared distance to avoid working out some slightly more complicated partial derivatives later.
The Lagrangian is
![L(x,y,z,\lambda)=(x-4)^2+y^2+(z+5)^2+\lambda(x+y+z-1)](https://tex.z-dn.net/?f=L%28x%2Cy%2Cz%2C%5Clambda%29%3D%28x-4%29%5E2%2By%5E2%2B%28z%2B5%29%5E2%2B%5Clambda%28x%2By%2Bz-1%29)
Take your partial derivatives and set them equal to 0:
![\begin{cases}\dfrac{\partial L}{\partial x}=2(x-4)+\lambda=0\\\\\dfrac{\partial L}{\partial y}=2y+\lambda=0\\\\\dfrac{\partial L}{\partial z}=2(z+5)+\lambda=0\\\\\dfrac{\partial L}{\partial\lambda}=x+y+z-1=0\end{cases}\implies\begin{cases}2x+\lambda=8\\2y+\lambda=0\\2z+\lambda=-10\\x+y+z=1\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7D%5Cdfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%20x%7D%3D2%28x-4%29%2B%5Clambda%3D0%5C%5C%5C%5C%5Cdfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%20y%7D%3D2y%2B%5Clambda%3D0%5C%5C%5C%5C%5Cdfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%20z%7D%3D2%28z%2B5%29%2B%5Clambda%3D0%5C%5C%5C%5C%5Cdfrac%7B%5Cpartial%20L%7D%7B%5Cpartial%5Clambda%7D%3Dx%2By%2Bz-1%3D0%5Cend%7Bcases%7D%5Cimplies%5Cbegin%7Bcases%7D2x%2B%5Clambda%3D8%5C%5C2y%2B%5Clambda%3D0%5C%5C2z%2B%5Clambda%3D-10%5C%5Cx%2By%2Bz%3D1%5Cend%7Bcases%7D)
Adding the first three equations together yields
![2x+2y+2z+3\lambda=2(x+y+z)+3\lambda=2+3\lambda=-2\implies \lambda=-\dfrac43](https://tex.z-dn.net/?f=2x%2B2y%2B2z%2B3%5Clambda%3D2%28x%2By%2Bz%29%2B3%5Clambda%3D2%2B3%5Clambda%3D-2%5Cimplies%20%5Clambda%3D-%5Cdfrac43)
and plugging this into the first three equations, you find a critical point at
![(x,y,z)=\left(\dfrac{14}3,\dfrac23,-\dfrac{13}3\right)](https://tex.z-dn.net/?f=%28x%2Cy%2Cz%29%3D%5Cleft%28%5Cdfrac%7B14%7D3%2C%5Cdfrac23%2C-%5Cdfrac%7B13%7D3%5Cright%29)
.
The squared distance is then
![d\left(\dfrac{14}3,\dfrac23,-\dfrac{13}3\right)^2=\dfrac43](https://tex.z-dn.net/?f=d%5Cleft%28%5Cdfrac%7B14%7D3%2C%5Cdfrac23%2C-%5Cdfrac%7B13%7D3%5Cright%29%5E2%3D%5Cdfrac43)
, which means the shortest distance must be
![\sqrt{\dfrac43}=\dfrac2{\sqrt3}](https://tex.z-dn.net/?f=%5Csqrt%7B%5Cdfrac43%7D%3D%5Cdfrac2%7B%5Csqrt3%7D)
.
(d): y = mx+n
m = -2/3 ⇒ y = (-2/3)x +n
A(-4, 6) ∈ d ⇒ 6 = (-2/3)·(-4) +n ⇒ 6 = 8/3 +n ⇒
⇒ n = 6 - 8/3 ⇒ n = 10/3
Now, we have:
y = (-2/3)x +10/3